2017
DOI: 10.1016/j.otsr.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of large diaphyseal bone defect by simplified bone transport over nail technique: A 7-case series

Abstract: Four-case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A subgroup of six studies 45 , 46 , 50 , 51 , 53 , 54 , 57 focusing on the bone transport approach showed a primary union rate of 89.7% with a mean external fixator time of 6.6 months (range 4.2–9.3 months), a complication rate of 66.9%, a reintervention rate of 29.8% and a failure rate of 3.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup of six studies 45 , 46 , 50 , 51 , 53 , 54 , 57 focusing on the bone transport approach showed a primary union rate of 89.7% with a mean external fixator time of 6.6 months (range 4.2–9.3 months), a complication rate of 66.9%, a reintervention rate of 29.8% and a failure rate of 3.7%.…”
Section: Resultsmentioning
confidence: 99%
“…The average bone defect was 8.8 cm (range 2.7–28 cm), and the average follow-up was 35.7 months (range 6–168 months). The Ilizarov method with external fixation was used in 15 studies 35 , 36 , 46 50 , 52 , 56 , 59 62 , 65 , intramedullary nailing and/or external fixation was used in eight studies 43 , 45 , 51 , 53 55 , 57 , 64 , a monolateral external fixation was used in one study 44 , and bone transport with a five-ring circular external fixator in one study 58 . One of the studies in the Ilizarov group was a case–control comparing bifocal versus trifocal fibular transfer, showing better primary union rate, fewer complications and reinterventions in the trifocal group.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic review by McMahon et al suggested that circular external fixation provides the most satisfactory results, with IM nailing, and open reduction internal fixation having higher rates of infection [ 6 ]. The use of ex-fix and bone lengthening with IM nail can have up to 50% complication rate including non-unions [ 7 , 8 ]. It is not only our experience but also the literature which demonstrates the use of Ilizarov as a “rescue procedure” in the treatment of tibial fractures when other techniques have failed [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, amputation, extremity disarticulation, and limb salvage procedures have all been utilized historically, with limb salvage techniques becoming increasingly prominent to maintain limb function and anatomy. Limb salvage becomes difficult as the tumor size and subsequent skeletal defect increases, thus necessitating allograft, autograft, or bone transport biologic means of skeletal reconstruction (Ferchaud et al, ; Yang et al, ). Although initially less morbid, allograft does not fully vascularize, resulting in a higher rate of nonunion, fractures, infection, and potentially further surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed the efficacy of bone transport methods to reconstruct large segmental defects in trauma, infection, and tumor, although there are limitations, including pin‐site infections, frequent office visits, and multiple procedures (Ferchaud et al, ; Yang et al, ). Further limitations of this technique in tumor cases are related to the effects of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%